The Role of Social Media in Increasing Sales in Resepi Village - Edy Yulianto Putra; Vina Liesty Indriani (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2023)
Kampung Recipe is a business in the food sector that sells traditional specialties. The product that is made is a homemade product that offers coconut roll semprong which has a sweet taste produced from palm sugar which gives a savory taste and thick coconut milk taste which is produced from pure coconut milk which makes the semprong taste have its own charm. The purpose of this community service program is to increase business sales. This program was carried out to introduce to millennials that semprong has many new and more diverse variations. This program uses qualitative methods by collecting data using observation, documentation, and interview methods. Based on the results of this community service program, it can be said that the application made can provide new opportunities in sales marketing by conveying the ideas that have been made. By providing information using snapgrams and tiktok with trending sounds and interesting movements.